The use of Drama in foreign Language Teaching and Learning in India: The Role of Drama in Enhancing Foreign Language Learning (Journal of Advances and Scholarly Researches in Allied Education, 2019)
We are living in a global world in which knowledge of a foreign language is important to decode and understand the most interesting and diverse cultural knowledge’s and languages. These days, Spanish is the second most spoken language and has become an important part of day to day life. This language is in use via mass of the major society, media, advertising, shopping, travelling etc. The situation becomes unavoidable when it comes of traveling and making oneself comfortable in the countries where the target language is being practiced. It gives a justifiable benefit to the young and dynamic learners considering the usage and benefit of the knowledge of target language. The knowledge of a foreign language helps in total personality improvement and primarily people learn it from the job prospective.The drama is a mean through which students shall be able to learn pronunciation, punctuation, expressions, reactions, gesture, body language, speaking, reading and many more. This is the one of the best method which works on communicative method as it focuses on use of the language in planned and unplanned situation. The ultimate goal of acquiring any language is to practice it in day to day life hence there can’t be any other method in which student is practicing all aspects of communication skills. Language acquisition at the University age can be compared from kids, they don’t learn the language however they acquire it and they speak the language perfectly. The use of drama as an innovative educational tool in foreign language learning teaching is decade's old approach which was started in the 19th century. Drama works on communicative approach and the Communicative Approach came into existence in 1970’s and since then the approach has been an important part of foreign language teaching. The fact is, tin India there are not many publications focused at study material creation based on drama based teaching.The drama is a process not a product and its ultimate goal is to convey the message to the targeted group in their own language. Undoubtedly, this tool satisfies fully all aspects of communication skills. This helps students in taking out their thoughts to the real world and it provides an opportunity to work on productive activity and enhances class participation. My strong belief is, drama plays a vital role in foreign language learning and teaching process. According to Via Few would disagree that drama has at last established itself as a means of helping people learn another language. A great deal of our everyday learning is acquired through experience, and in the language, classroom drama fulfils that experiential need (1987, pp110).